2002
DOI: 10.1038/sj.bdj.4801478a
|View full text |Cite
|
Sign up to set email alerts
|

Food and drink consumption, sociodemographic factors and dental caries in 4–5-year-old children in Amman, Jordan

Abstract: Objective To investigate the association between type of food and drink consumption, sociodemographic factors and prevalence and severity of caries in 4-5-year-old Jordanian children. Method Two-stage random sampling procedure was used to select children enrolled in kindergartens in Amman. Clinical examinations were carried out by one examiner. Mothers completed a questionnaire relating to sociodemographic factors and food and drink consumption. Results Snack foods were consumed by a high percentage of childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
1
4

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 14 publications
5
13
1
4
Order By: Relevance
“…The current study’s findings clearly show that those children who consumed soft drinks three times or more per day had a higher mean dmft score than those who consumed it less than twice per week. This is consistent with other studies from the Middle East (11, 27). About one in four of the children who participated in the survey consumed soft drinks.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The current study’s findings clearly show that those children who consumed soft drinks three times or more per day had a higher mean dmft score than those who consumed it less than twice per week. This is consistent with other studies from the Middle East (11, 27). About one in four of the children who participated in the survey consumed soft drinks.…”
Section: Discussionsupporting
confidence: 94%
“…A study of 4–6‐yr‐old children in Saudi Arabia reported that a high percentage (88%) regularly consumed sweet snacks (20), and S ayegh et al. (11) reported that confectionery was eaten regularly by 76% of Jordanian 4–5‐yr‐old children. The current study was able to determine that most of the snacks consumed by the children were sugary in nature, and the association found between caries severity and the daily frequency of snacking between meals was consistent with findings from other studies (15, 21, 22), although it is recommended by the WHO (http://www.who.int/oral_health/action/risks/en/index.html) that the frequency of sugar intake should be limited to a maximum of four times per day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies showed a positive relationship between caries and dental erosion and the consumption of soft drinks (Sayegh et al, 2002;Johansson et al, 1996;Harding et al, 2003;Al-Majed et al, 2002;Luo et al, 2005). Accordingly, the clinical manifestations and diagnosis of diseases caused by soft drinks should be regarded as a combination of erosion and caries, and clinicians should pay more attention to it.…”
Section: Introductionmentioning
confidence: 99%